Preparation of halogenated polycyclic aromatic hydrocarbon pre-sodium modification agent and application of halogenated polycyclic aromatic hydrocarbon pre-sodium modification agent in biomass hard carbon negative electrode
By using halogenated polycyclic aromatic hydrocarbons and metal sodium in ether solvents, an organometallic solution is formed to pre-sodiumize the hard carbon negative electrode of sodium ion battery biomass, solving the problems of low initial Coulomb efficiency and insufficient cycle life, realizing the Efficient battery performance improvement.
Patent Information
- Application Number
- CN202411322199.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-02-11
AI Technical Summary
The initial Coulombic efficiency and insufficient cycle life of the biomass hard carbon anode of sodium ion batteries.
Halogenated polycyclic aromatic hydrocarbons are used as pre-sodiumizing agents to form an organometallic solution to pre-sodiumization of the electrodes by reacting with sodium metal in an ether solvent. This method can control the reaction degree and rate, avoid excessive prenatination and structural damage to the electrode.
The initial Coulombic efficiency (ICE) of sodium ion batteries was significantly improved to 90%, and the capacity retention rate increased from 68% to 93% after 100 cycles, improving the cycle stability and electrochemical performance of the battery.
Smart Images

Figure CN119419268A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery negative electrodes, and specifically relates to the preparation of biomass hard carbon negative electrode materials, and in particular to the preparation and application of a halogenated polycyclic aromatic hydrocarbon pre-sodiumization agent. Background Art
[0002] Sodium ion battery (SIB), as a new energy storage system, has broad application prospects. Biomass hard carbon is considered to be an indispensable part of the practical application of SIB due to its low cost, low redox potential and high capacity. At present, biomass hard carbon negative electrode is still subject to bottlenecks such as low initial coulombic efficiency (ICE) and insufficient cycle life. Therefore, the development of efficient pre-sodiumization technology to compensate for the low ICE and assist in building a stable interface to facilitate long-term circulation is expected to accelerate the practical application of SIB. Contents of the invention
[0003] The purpose of the present invention is to solve the problems of low initial coulombic efficiency and insufficient cycle life of biomass hard carbon negative electrode of sodium ion battery, and provide a preparation of halogenated polycyclic aromatic hydrocarbon pre-sodium agent and its application in biomass hard carbon negative electrode. Alkali metals can spontaneously react with polycyclic aromatic hydrocarbons (PAHs) in ether solvents at room temperature to form an organic metal solution with strong reducing property, which is used for pre-sodiumization of electrodes. However, the pre-sodiumization agents mainly based on PAHs with conjugated large π bonds often have strong reducing properties, which can easily cause excessive pre-sodiumization of electrodes and even structural damage to the electrodes themselves. Therefore, it is necessary to develop new pre-sodiumization agents with controllable reaction degree and reaction rate. In halogenated polycyclic aromatic hydrocarbons (H-PAHs) molecules, halogen heteroatoms can play an electron-withdrawing induction effect and a conjugation effect, which reduces the electron cloud density on the aromatic ring and reduces the reaction rate in the pre-sodiumization process to a certain extent. At the same time, halogens can assist the uniform formation of solid electrolyte interface film (SEI) in the first cycle, which is beneficial to the high reversibility and stable cycle of batteries.
[0004] The technical solution of the present invention is:
[0005] The preparation method of a polycyclic aromatic hydrocarbon pre-sodiumizing agent comprises the following preparation steps:
[0006] (1) Preparation of pre-sodiumization agent: halogenated polycyclic aromatic hydrocarbons (H-PAHs) are placed in an ether solvent and stirred continuously at room temperature until completely dissolved, the reaction time is 5 to 10 minutes, and after being mixed evenly, an H-PAHs / ether solution is obtained; metallic sodium (Na) is added to the H-PAHs / ether solution and stirred thoroughly, the reaction time is 2 to 4 hours, and then allowed to stand for 20 to 30 minutes, and finally an H-PAHs / Na / ether pre-sodiumization agent is obtained;
[0007] (2) Preparation of biomass hard carbon negative electrode: Place microcrystalline cellulose powder in a high-temperature tube furnace and carbonize it in an inert protective gas atmosphere at a reaction temperature of 1000-1200°C for 2-3 hours to obtain a biomass hard carbon negative electrode material (M-HC). Mix M-HC, conductive carbon black and binder in water at a mass ratio of 8:1:1 and stir for 2-3 hours. After it is made into a uniform slurry, it is scraped on an aluminum foil current collector and placed in a blast drying oven at 80-100°C for 8-10 hours. Finally, the dried electrode is cut into discs with a diameter of 10 mm using a cutting machine.
[0008] (3) Pre-sodiumization of hard carbon negative electrode: The prepared hard carbon negative electrode is soaked in H-PAHs / Na / ether pre-sodiumization agent for pre-sodiumization, and the reaction time is 15 to 30 minutes. The working electrode is rinsed with ethylene glycol dimethyl ether and placed in a vacuum oven at 70°C for 15 to 30 minutes until it is completely dry to obtain a pre-sodiumized hard carbon negative electrode.
[0009] In the steps, the polycyclic aromatic hydrocarbons are one of dimethyl ether or ethylene glycol dimethyl ether; the molar concentration of halogenated polycyclic aromatic hydrocarbons in the ether solvent is 0.1-0.5 mol / L, and the molar ratio of metallic sodium to halogenated polycyclic aromatic hydrocarbons is 2-3:1; the particle size range of the microcrystalline cellulose is 70-140 μm; the heating rate is 2-3°C / min; the inert protective gas can be one of nitrogen or argon; the conductive carbon black can be one of SuperP or Ketjen black; the binder can be one of sodium carboxymethyl cellulose or sodium alginate; in the pre-sodiumization reaction environment of the hard carbon negative electrode, the water and oxygen contents are respectively <0.01 ppm; the pressure setting interval of vacuum drying is -0.1-0.05 MPa.
[0010] The present invention also provides the use of a pre-sodiumized hard carbon negative electrode in a sodium ion battery, and the method is as follows:
[0011] (3) Battery assembly: The negative electrode was assembled with sodium metal into a two-electrode system in a glove box. The battery assembly model was a CR2032 button cell.
[0012] In the application, the negative electrode can be a biomass hard carbon negative electrode or a pre-sodiumized biomass hard carbon negative electrode; the water and oxygen contents in the glove box are respectively less than 0.01 ppm; and the sodium metal electrode has a diameter of 12 to 14 mm.
[0013] The advantages and beneficial effects of the present invention are:
[0014] The pre-sodiumization agent is an organic metal solution with good safety, and the negative electrode pre-sodiumization process is simple. It only requires simple immersion and does not require excessive treatment, making it suitable for large-scale production. Compared with solid-phase pre-sodiumization, liquid-phase sodiumization reagents can ensure uniform and sufficient pre-sodiumization of the hard carbon negative electrode. At the same time, halogen atoms can assist in the uniform formation of the solid electrolyte interface film (SEI) in the first cycle, which is beneficial to the battery to improve ICE and stability. Electrochemical tests based on biomass hard carbon negative electrodes show that after treatment with halogenated polycyclic aromatic hydrocarbon pre-sodiumization agents, the battery ICE can be significantly increased to 90%, and after 100 cycles, the capacity retention rate is increased from 68% to 93%, showing excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is the XRD pattern of the prepared biomass hard carbon negative electrode material.
[0016] Figure 2 This is the cycling performance of the biomass hard carbon negative electrode at a current density of 100 mA / g.
[0017] Figure 3 The cycling performance of the pre-sodiumized biomass hard carbon anode at a current density of 100 mA / g.
[0018] Figure 4 These are the first cycle charge and discharge curves of different biomass hard carbon anodes at a current density of 100 mA / g.
[0019] Figure 5 It is a comparative diagram, (a) is the first cycle charge and discharge curve of the biomass hard carbon negative electrode after pre-sodiumization with naphthalene / Na / DME at a current density of 100 mA / g; (b) is the cycle performance of the biomass hard carbon negative electrode after pre-sodiumization in naphthalene / Na / DME. DETAILED DESCRIPTION
[0020] Example 1
[0021] (1) Preparation of pre-sodium agent: 0.125 mol of 1-fluoronaphthalene was mixed with 500 mL of tetrahydrofuran (THF) and stirred continuously at room temperature until completely dissolved, and the reaction time was 5 min to prepare a 0.25 mol / L 1-fluoronaphthalene / ether solution; 0.25 mol of metallic sodium (Na) was added to the 1-fluoronaphthalene / ether solution and stirred sufficiently, and the reaction time was 2 h. Then, the solution was allowed to stand for 20 min to finally obtain a 1-fluoronaphthalene / Na / THF pre-sodium agent.
[0022] (2) Preparation of biomass hard carbon negative electrode: Place microcrystalline cellulose powder with a particle size of 90 μm in a high-temperature tube furnace and carbonize it under an argon protective gas atmosphere. The reaction temperature is 1100°C and maintained for 2 hours to obtain a biomass hard carbon negative electrode material (M-HC). M-HC, Ketjen black and sodium alginate binder are mixed in water at a mass ratio of 8:1:1 and stirred for 2 hours. After it is made into a uniform slurry, it is scraped on the aluminum foil current collector and placed in an 80°C forced air drying oven for 10 hours. Finally, the dried electrode is cut into discs with a diameter of 10 mm using a cutting machine.
[0023] (3) Pre-sodiumization of hard carbon negative electrode: The prepared hard carbon negative electrode was immersed in 1-fluoronaphthalene / Na / THF pre-sodiumization agent for 20 min; after taking out, the immersed working electrode was rinsed with THF and placed in a 70°C vacuum oven for 20 min until completely dry to obtain a pre-sodiumized hard carbon negative electrode.
[0024] Example 2
[0025] (1) Preparation of pre-sodium agent: 0.05 mol of 2-fluorobiphenyl was stirred continuously in 100 mL of tetrahydropyran (THP) at room temperature until completely dissolved, and the reaction time was 10 min to prepare a 0.5 mol / L 2-fluorobiphenyl / THP solution; 0.15 mol of metallic sodium (Na) was added to the 2-fluorobiphenyl / THP solution and stirred thoroughly, and the reaction time was 2.5 h. Then, the solution was allowed to stand for 30 min to finally obtain a 2-fluorobiphenyl / Na / THP pre-sodium agent.
[0026] (2) Preparation of biomass hard carbon negative electrode: Place microcrystalline cellulose powder with a particle size of 120 μm in a high-temperature tube furnace and carbonize it under an argon protective gas atmosphere. The reaction temperature is 1200°C and maintained for 2.5 hours to obtain a biomass hard carbon negative electrode material (M-HC). M-HC, SuperP and sodium carboxyethyl cellulose binder are mixed evenly in water at a mass ratio of 8:1:1 and stirred for 3 hours. After it is made into a uniform slurry, it is scraped on the aluminum foil current collector and placed in a 100°C forced air drying oven for 8 hours. Finally, the dried electrode is cut into discs with a diameter of 10 mm using a cutting machine.
[0027] (3) Pre-sodiumization of hard carbon negative electrode: The prepared hard carbon negative electrode was immersed in 2-fluorobiphenyl / Na / THP pre-sodiumization agent for 15 min. After taking it out, the immersed working electrode was rinsed with THP and placed in a vacuum oven at 70 °C for 30 min until it was completely dry to obtain a pre-sodiumized hard carbon negative electrode.
[0028] Example 3
[0029] (1) Preparation of pre-sodium agent: 0.025 mol of 1-chloromethylnaphthalene was stirred continuously in 250 mL of ethylene glycol dimethyl ether (DME) at room temperature until completely dissolved, and the reaction time was 8 min to prepare 0.1 mol / L 1-chloromethylnaphthalene / DME solution; 0.075 mol of metallic sodium (Na) was added to the 1-chloromethylnaphthalene / DME solution and stirred thoroughly, and the reaction time was 3 h. Then, the solution was allowed to stand for 30 min to finally obtain 1-chloromethylnaphthalene / Na / DME pre-sodium agent.
[0030] (2) Preparation of biomass hard carbon negative electrode: Place microcrystalline cellulose powder with a particle size of 140 μm in a high-temperature tube furnace and carbonize it under an argon protective gas atmosphere. The reaction temperature is 1200°C and maintained for 3 hours to obtain a biomass hard carbon negative electrode material (M-HC). M-HC, Ketjen black and sodium alginate binder are mixed in water at a mass ratio of 8:1:1 and stirred for 2.5 hours. After it is made into a uniform slurry, it is scraped on the aluminum foil current collector and placed in a 90°C forced air drying oven for 10 hours. Finally, the dried electrode is cut into discs with a diameter of 10 mm using a cutting machine.
[0031] (3) Pre-sodiumization of hard carbon negative electrode: The prepared hard carbon negative electrode was immersed in 1-chloromethylnaphthalene / Na / DME pre-sodiumization agent for 30 min; after taking out, the immersed working electrode was rinsed with DME and placed in a 70 °C vacuum oven for 20 min until completely dry to obtain a pre-sodiumized hard carbon negative electrode.
[0032] Example 4: Battery Assembly
[0033] First, in a glove box with water and oxygen content <0.01ppm respectively, the pre-sodiumized hard carbon negative electrode and sodium metal are used to form a two-electrode system, and the battery assembly model is CR2032 button battery. Sodium hexafluorophosphate (NaPF6) is dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) (volume ratio of 1:1:1) as the electrolyte; a glass fiber with a diameter of 16mm is used as the diaphragm, and a metal sodium sheet with a diameter of 14mm is used as the counter electrode. The entire assembly process is completed in a glove box with an argon atmosphere, and the voltage test range is 0.01~2.5V (vs.Na / Na + ).
[0034] Figure 1 The XRD pattern of the prepared biomass hard carbon negative electrode material shows that two diffraction peaks appear at 2θ=22° and 43°, corresponding to the (002) and (100) crystal planes in the disordered carbon, respectively.
[0035] Figure 2The cycling performance of the biomass hard carbon anode at a current density of 100 mA / g. The test results show that the specific capacity of the biomass hard carbon anode gradually decays in the ester electrolyte. After 100 cycles, the capacity retention rate is 62%, while the ICE is only 68%. This is attributed to the unstable formation of the first SEI, which causes Na + Excessive losses.
[0036] Figure 3 The cycling performance of the pre-sodiumized biomass hard carbon anode at a current density of 100 mA / g. The test shows that after a one-step pre-sodiumization treatment, the cycling stability has been significantly improved. After 100 cycles, the capacity retention rate has increased to 93%, and the ICE has been significantly improved to 90%.
[0037] Figure 4 The first cycle charge and discharge curves of different biomass hard carbon negative electrodes at a current density of 100mA / g. By comparison, it can be seen that the hard carbon negative electrode treated with pre-sodium treatment can increase the ICE from 68% to 90%. At the same time, the open circuit voltage corresponding to the initial discharge of the first cycle is significantly reduced, proving that the negative electrode is reduced by the pre-sodium agent to a certain extent, achieving effective sodium supplementation.
[0038] Comparative Example
[0039] (1) Preparation of pre-sodium agent: 0.05 mol of naphthalene was stirred continuously in 250 mL of ethylene glycol dimethyl ether (DME) at room temperature until completely dissolved, and the reaction time was 8 min to prepare a 0.2 mol / L naphthalene / DME solution; 0.125 mol of metallic sodium (Na) was added to the naphthalene / DME solution and stirred thoroughly, and the reaction time was 2 h. Then, the solution was allowed to stand for 30 min to finally obtain a naphthalene / Na / DME pre-sodium agent.
[0040] (2) Preparation of biomass hard carbon negative electrode: Place microcrystalline cellulose powder with a particle size of 140 μm in a high-temperature tube furnace and carbonize it under an argon protective gas atmosphere. The reaction temperature is 1200°C and maintained for 3 hours to obtain a biomass hard carbon negative electrode material (M-HC). M-HC, Ketjen black and sodium alginate binder are mixed evenly in water at a mass ratio of 8:1:1 and stirred for 3 hours. After it is made into a uniform slurry, it is scraped on the aluminum foil current collector and placed in a 90°C forced air drying oven for 10 hours. Finally, the dried electrode is cut into discs with a diameter of 10 mm using a cutting machine.
[0041] (3) Pre-sodiumization of hard carbon negative electrode: The prepared hard carbon negative electrode was soaked in naphthalene / Na / DME pre-sodiumization agent for 30 min; after taking out, the soaked working electrode was rinsed with DME and placed in a 70°C vacuum oven for 20 min until completely dry to obtain a pre-sodiumized hard carbon negative electrode.
[0042] Figure 5(a) is the first cycle charge and discharge curve of different biomass hard carbon negative electrodes at a current density of 100mA / g. By comparison, it can be seen that the hard carbon negative electrode that has been pre-sodiumized can increase the ICE from 68% to 89%. At the same time, the open circuit voltage corresponding to the initial discharge of the first cycle is significantly reduced, proving that the negative electrode is reduced by the pre-sodiumizing agent to a certain extent. (b) is the cycle performance of the biomass hard carbon negative electrode after pre-sodiumization in naphthalene / Na / DME. It can be seen from the figure that in this system, although the ICE is improved to a certain extent, the reaction activity of the pre-sodiumizing agent is too high, causing the electrode structure to be destroyed, resulting in insufficient cycle stability. Therefore, in the present invention, the pre-sodiumizing agent based on halogenated polycyclic aromatic hydrocarbons can achieve better pre-sodiumization effect.
Claims
1. A method for preparing a halogenated polycyclic aromatic hydrocarbon pre-sodiumizing agent, characterized in that The method comprises the following preparation steps: (1) Preparation of pre-sodiumization agent: placing halogenated polycyclic aromatic hydrocarbons H-PAHs in an ether solvent and stirring continuously at room temperature for 5 to 10 minutes, and after mixing evenly, obtaining an H-PAHs / ether solution; adding metallic sodium Na to the H-PAHs / ether solution and stirring thoroughly for 2 to 4 hours, and then standing for 20 to 30 minutes, and finally obtaining an H-PAHs / Na / ether pre-sodiumization agent; (2) Preparation of biomass hard carbon negative electrode: Place microcrystalline cellulose powder in a high-temperature tube furnace and carbonize it in an inert protective gas atmosphere at a reaction temperature of 1000-1200°C for 2-3 hours to obtain a biomass hard carbon negative electrode material M-HC. Mix M-HC, conductive carbon black and binder in water at a mass ratio of 8:1:1 and stir for 2-3 hours. After it is made into a uniform slurry, it is scraped on an aluminum foil current collector and placed in a blast drying oven at 80-100°C for 8-10 hours. Finally, the dried electrode is cut into discs with a diameter of 10 mm using a cutting machine; (3) Pre-sodiumization of biomass hard carbon negative electrode: The biomass hard carbon negative electrode is soaked in H-PAHs / Na / ether pre-sodiumization agent for pre-sodiumization, and the reaction time is 15 to 30 minutes. The working electrode is rinsed with ethylene glycol dimethyl ether and placed in a vacuum oven at 70°C for 15 to 30 minutes until it is completely dry to obtain a pre-sodiumized biomass hard carbon negative electrode.
2. The preparation method of the pre-sodiumizing agent according to claim 1, wherein In step (1), the molar concentration of the halogenated polycyclic aromatic hydrocarbons in the ether solvent is 0.1-0.5 mol / L, and the molar ratio of metallic sodium to the halogenated polycyclic aromatic hydrocarbons is 2-3:
1.
3. The preparation method of the pre-sodiumizing agent according to claim 1, wherein The halogenated polycyclic aromatic hydrocarbon is one of 1-fluoronaphthalene, 2-fluorobiphenyl or 1-chloromethylnaphthalene; the ether solvent is one of tetrahydrofuran, tetrahydropyran or ethylene glycol dimethyl ether.
4. The preparation method of the pre-sodiumizing agent according to claim 1, wherein In step (2), the particle size of microcrystalline cellulose is in the range of 70 to 140 μm; the heating rate is 2 to 3° C. / min; the inert protective gas is one of nitrogen or argon; the conductive carbon black is one of SuperP or Ketjen black; and the binder is one of sodium carboxymethyl cellulose or sodium alginate.
5. The preparation method of the pre-sodiumizing agent according to claim 1, wherein In step (3), the water and oxygen contents in the reaction environment are respectively less than 0.01 ppm; and the pressure setting range of the vacuum drying is -0.1 to 0.05 MPa.
6. A halogenated polycyclic aromatic hydrocarbon pre-sodiumizing agent, characterized in that: It is prepared by the method according to any one of claims 1 to 5.
7. Use of the halogenated polycyclic aromatic hydrocarbon pre-sodiumization agent according to claim 6 in a biomass hard carbon negative electrode for a sodium ion battery.
Citation Information
Patent Citations
Rechargeable organosodium polymer battery
CN103828103A
Modified alkali metal ion battery negative plate as well as preparation method and application thereof
CN113130853A
Modification method and application of Prussian blue material
CN117800359A
Pre-sodium modification method and application of sodium ion battery positive electrode material
CN118431418A
Sodium secondary battery
US20140050974A1
Cited By
Sodium supplementing method of sodium ion battery hard carbon negative electrode material
CN121215765A